The crystallization behavior of amorphous Ge2Sb2Te5 films induced by a multi-pulsed nanosecond laser. (3rd August 2017) - Fan, T; Liu, F R; Li, W Q; Guo, J C; Wang, Y H; Sun, N X; Liu, F
Abstract: In this paper, accumulated crystallization of amorphous Ge2 Sb2 Te5 (a-GST) films induced by a multi-pulsed nanosecond (ns) excimer laser was investigated by x-ray diffraction (XRD), atomic force microscopy, field-emission scanning electron microscopy, x-ray photoelectron spectroscopy (XPS) and a spectrophotometer. XRD analyses revealed that detectable crystallization was firstly observed in the preferred orientation (200), followed by the orientations (220) and (111) after two pulses. Optical contrast, determined by crystallinity as well as surface roughness, was found to retain a linear relation within the first three pulses. A layered growth mechanism from the top surface to the interior of a-GST films was used to explain the crystallization behavior induced by the multi-pulse ns laser. XPS analyses for bond rearrangement and electronic structure further suggested that the crystallization process was performed by generating new bonds of Ge–Te and Sb–Te after laser irradiations. This paper presents the potential of multi-level devices and tunable thermal emitters based on controllable crystallization of phase-change materials.